Recurrent Infections in a Patient with Multiple Myeloma - Kini, Sanjay; Shanbhag, Aravind; Chandramohan, Sachin (Journal of Health and Allied Sciences NU, 2019)
An 80-year-old woman with recurrent urinary tract infection presented to the orthopaedic OPD at KS Hegde Memorial Health Center, Bailur, with gradual onset of generalized weakness, fatigue, anorexia, musculoskeletal pain, and particularly severe backache. The patient was diagnosed to have anemia but renal function tests were normal. X-ray spine showed multiple compression fractures. Serum electrophoresis confirmed the diagnosis of multiple myeloma. In an elderly patient with myalgia, anemia, and recurrent infections, the differential diagnosis of multiple myeloma should be kept in mind as it is often missed by clinicians.
Keywords: multiple myeloma; anemia; β2-microglobulin